Monitoring Heat Treatments in Steels by a Non Destructive Ultrasonic Method - Monsalve-Gonzalez, A; Carvajal-Ortega, L; Artigas-Abuin, A (Universidade Federal de Sao Carlos, 2017)
In order to determine if heat treatments can be discerned by nondestructive ultrasonic testing, samples of SAE 1045 and SAE 4140 steels were subjected to the classical heat treatments of annealing, normalizing, quenching, and quenching and tempering, and their elastics constants, Young s, shear and Poisson s moduli, were monitored by ultrasound. Results show that the microstructural differences associated to the various heat treatments generate differences on the elastic constants that can be effectively discerned by the use of longitudinal and shear ultrasonic waves. Special attention is given to Poisson s modulus, since for its determination only times of flight of longitudinal and shear ultrasonic waves, and not the distance the waves travel, are required, which is of quite practical importance, since measurements are simplified and a fundamental source of error is eliminated. It is thus shown that the microstructural evolution of a steel part subjected to heat treatments can be monitored by this simple ultrasonic method. © 2017 Universidade Federal de Sao Carlos. All rights reserved.